Tribotechnical the characteristics composite steel powders sh15 obtained from waste engineering - Гальчук, Т.Н. (Problems of Tribology, 2014)
The investigated the tribological properties of powder steel SH15 and powder composites on its basis with the content of copper and graphite. Based on experimental data set from dependence of the tribological properties from the compacting pressure and sintering temperature. It is shown the prospects of the composite powder as an antifriction material.